Perception and utilization of traditional birth attendants by pregnant women attending primary health care clinics in a rural Local Government Area in Ogun State, Nigeria - Ebuehi OM; Akintujoye IA (Dove Medical Press, 2012)
Olufunke M Ebuehi, IA AkintujoyeReproductive and International Health Unit, Department of Community Health and Primary Care, College of Medicine, University of Lagos, Lagos, NigeriaBackground: In developing countries, most childbirth occurs at home and is not assisted by skilled attendants. This situation increases the risk of death for both mother and child and has severe maternal and neonatal health complications. The purpose of this study was to explore pregnant women’s perceptions and utilization of traditional birth attendant (TBA) services in a rural Local Government Area (LGA) in Ogun State, southwest Nigeria.Methods: A quantitative design was used to obtain information using a structured questionnaire from 250 pregnant women attending four randomly selected primary health care clinics in the LGA. Data were analyzed using Epi Info (v 3.5.1) statistical software.Results: Almost half (48.8%) of the respondents were in the age group 26–35 years, with a mean age of 29.4 ± 7.33 years. About two-thirds (65.6%) of the respondents had been pregnant 2–4 times before. TBA functions, as identified by respondents, were: “taking normal delivery” (56.7%), “providing antenatal services” (16.5%), “performing caesarean section” (13.0%), “providing family planning services” (8.2%), and “performing gynaecological surgeries” (5.6%). About 6/10 (61.0%) respondents believed that TBAs have adequate knowledge and skills to care for them, however, approximately 7/10 (69.7%) respondents acknowledged that complications could arise from TBA care. Services obtained from TBAs were: routine antenatal care (81.1%), normal delivery (36.1%), “special maternal bath to ward off evil spirits” (1.9%), “concoctions for mothers to drink to make baby strong” (15.1%), and family planning services (1.9%). Reasons for using TBA services were: “TBA services are cheaper” (50.9%), “TBA services are more culturally acceptable in my environment” (34.0%), “TBA services are closer to my house than hospital services” (13.2%), “TBAs provide more compassionate care than orthodox health workers” (43.4%), and “TBA service is the only maternity service that I know” (1.9%). Approximately 8/10 (79.2%) of the users (past or current) opined that TBA services are effective but could be improved with some form of training (78.3%). More than three-quarters (77.1%) opposed the banning of TBA services. Almost 7/10 (74.8%) users were satisfied with TBA services.Conclusion: Study findings revealed a positive perception and use of TBA services by the respondents. This underlines the necessity for TBAs’ knowledge and skills to be improved within permissible standards through sustained partnership between TBAs and health systems. It is hoped that such partnership will foster a healthy collaboration between providers of orthodox and traditional maternity services that will translate into improved maternal and neonatal health outcomes in relevant settings.Keywords: traditional birth attendants, TBA services, pregnant women, utilization of TBA services